A study on mixed fracture characteristics of composite single lap joint (SLJ) combining mixed continuum damage model and critical zone size based approach. (December 2019) - Kim, Myong-Ho; Ri, Jun-Hyok; Hong, Hyon-Sik
Abstract: In this paper, authors present an improved method for predicting the mixed fracture characteristics of composite single lap joint using the mixed - mode continuum damage model and the critical zone size based approach. We apply a method based on the critical zone size to predict the failure of composite adherend and establish a procedure for more precisely calculating the critical zone size using the ABAQUS user subroutine. In addition, a bilinear/exponential mixed - mode continuum damage model is used to evaluate the failure of adhesive of single lap joint. The failure of adherend and the damage process of adhesives can be considered simultaneously by the method based on the critical zone size and the mixed - mode continuum damage model. For the validation of proposed model, the user subroutine of general purpose finite element software ABAQUS was used to simulate the failure process of single lap joint made of fiber reinforced composite materials and the obtained results were compared with the previous experimental results. The results obtained by the method presented in this paper are in good agreement with previous experimental results, and showed that the adhesive cohesive damage process before the global failure of the joint due to the failure of the adherend and the interlayer failure of the composite adherend can be predicted simultaneously.